2009
DOI: 10.1007/s00268-008-9912-2
|View full text |Cite
|
Sign up to set email alerts
|

Patency Rates of Cuffed and Noncuffed Extended Polytetrafluoroethylene Grafts in Dialysis Access: A Prospective, Randomized Study

Abstract: This investigation revealed that the cuffed ePTFE graft, which was designed to decrease graft outlet stenosis, may enhance the clinical patency rates of dialysis grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
0
29
1
Order By: Relevance
“…9 The clinical application of the Venaflo grafts showed some improvements of the long term patency, however, there are still a number of cases in which significant venous stenosis has developed, and the overall results remain unfavorable. 10,11,13 The main drawback of a funnel-shaped anastomotic geometry is that in anastomotic expansions, separation areas develop invariably. This is a well known fluid mechanical principle of pipe flows where a sudden expansion of more than 6°to 7°is introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The clinical application of the Venaflo grafts showed some improvements of the long term patency, however, there are still a number of cases in which significant venous stenosis has developed, and the overall results remain unfavorable. 10,11,13 The main drawback of a funnel-shaped anastomotic geometry is that in anastomotic expansions, separation areas develop invariably. This is a well known fluid mechanical principle of pipe flows where a sudden expansion of more than 6°to 7°is introduced.…”
Section: Discussionmentioning
confidence: 99%
“…9 After the clinical introduction of the Venaflo grafts, however, the long-term patency of cuffed arteriovenous PTFE grafts remained poor. [10][11][12][13] This presumably is because the Venaflo graft has a wide cuffed outflow section that effectively reduces the shear forces, but as a result of the sudden anastomotic expansion, simultaneously promotes the creation of flow separation areas near the PTFE wall. In pipe flow, a flow separation invariably occurs when the mainstream-to-wall angle suddenly extends to more than 6°to 8°.…”
mentioning
confidence: 98%
“…Previous clinical data to date to support such an intervention comes from several studies evaluating cuffed AVG grafts ("Venaflo"; Bard Vascular, Tempe Arizona) [208][209][210] . In a recent randomized control trial evaluating cuffed vs non-cuffed AVG, cuffed AVGs showed better primary patency and cumulative survival 211 . Finally, results from a newly developed anastomotic implant device, "OptiflowTM" (Bioconnect Systems; Ambler, PA), to connect the artery and vein in AVFs and improve hemodynamics by providing a symmetric flow pattern, have shown a primary patency of 83% at 90 days 212 .…”
Section: Improving Hemodynamicsmentioning
confidence: 99%
“…Hence, the long-term results of the Venaflo graft are equally dissatisfying as those of the straight grafts. 4,7 Several in vitro and computational fluid dynamics studies aimed to describe the complex hemodynamics of arteriovenous graft anastomoses. [8][9][10][11][12] The complexity of the hemodynamics of av-anastomoses results from the connection of high-pressure high-velocity arterial flow to a lowpressure low-velocity venous circulation.…”
mentioning
confidence: 99%
“…[1][2][3] Currently, two different graft configurations are available, the straight uncuffed ePTFE graft and the cuffed Venaflo graft (Bard, Tempe, Ariz). 4 While the Venaflo prosthesis features a venous cuff expansion, for straight grafts, standard 6 to 7 mm PTFE prostheses without any anastomotic modifications are used. There are several variations of the ePTFE wall of straight grafts available, but currently only the Venaflo graft uses a diameter variation as a design feature.…”
mentioning
confidence: 99%